The expansion of Dublin and the policy implications of dispersal - Williams, Brendan; Shiels, Patrick (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2002)
While the process of economic globalisation has presented the region with significant opportunities the future and continuing economic development of the region is also threatened by global exposure of the export orientated sectors in the face of economic downturn. Nevertheless, there remains a broad consensus to develop a high knowledge-based and high technology based productive sector. The initial trend in 2001 is that while the new economy downturn has resulted in job losses and closures such as Gateway, Motorola and others the current skills and labour shortages have seen significant numbers of such staff immediately re-employed elsewhere. Future economic prospects since the September 11th terrorist attacks on the USA are considerably more uncertain. Whether this scenario continues is of course open to question.
Keywords: Urban geography -- Ireland